Effect of Salinity on Growth and Vitamin C Content of Aloe Vera (Aloe vera L.) - Uswatunnisa Uswatunnisa; Wardiah Wardiah; Supriatno Supriatno (Jurnal Ilmiah Mahasiswa Pendidikan Biologi, 2017)
Study about